Improving Construction Process through Integration and Concurrent Engineering (Construction Economics and Building, 2012)
In an increasingly competitive business environment, improvedtime-to-market, reduced production cost, quality of the productand customer involvement are rapidly becoming the key successfactors for any product development process. Consequently, mostorganisations are moving towards the adoption of latest technologyand new management concepts and philosophies such as totalquality management and concurrent engineering (CE) to bringimprovement in their product development process. This paperdiscusses the adoption of integrated processes and CE withinthe construction industry to enable construction organisations toimprove their project development process. It also discusses aproposed integrated database model for the construction projects,which should enable the construction process to improve, becomemore effective and more efficient.